1997
DOI: 10.1002/art.1780400424
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Hodgkin's lymphoma and other cancers among a cohort of patients with systemic lupus erythematosus

Abstract: 5.2, 95% confidence interval 2.2-10.3). In addition, a significantly increased RR was found for cancer of the lung (RR 1.9; n = 15)' the liver (RR 8.0; n = 5)' and the vagina/vulva (RR 5.7; n = 3).Conclusion. There seemed to be a positive association between SLE and non-Hodgkin's lymphoma.Other cancers with a possible virus-related etiology, such as liver and vaginalhlva cancer, were also observed in excess. In addition, there was an indication of an increased risk of lung cancer among patients who were hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
192
2
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(211 citation statements)
references
References 34 publications
(26 reference statements)
11
192
2
6
Order By: Relevance
“…Other shortcomings include the use of NHL classifications preceding the recently introduced WHO classification (41) and the lack of information on treatments of autoimmune diseases, such as immunosuppressive therapy. Previous Scandinavian studies based on hospital and cancer registries have evaluated cancer risk among persons with single autoimmune conditions but were generally limited by the small number of NHL outcomes (42)(43)(44)(45)(46)(47)(48)(49)(50). Family history of RA and risk of NHL was assessed in a registry-based study from Sweden (42).…”
Section: Discussionmentioning
confidence: 99%
“…Other shortcomings include the use of NHL classifications preceding the recently introduced WHO classification (41) and the lack of information on treatments of autoimmune diseases, such as immunosuppressive therapy. Previous Scandinavian studies based on hospital and cancer registries have evaluated cancer risk among persons with single autoimmune conditions but were generally limited by the small number of NHL outcomes (42)(43)(44)(45)(46)(47)(48)(49)(50). Family history of RA and risk of NHL was assessed in a registry-based study from Sweden (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, immunosuppressive therapy may negatively impact a patient's condition when he or she has an underlying infection. In addition, extra caution must be taken in the case of coexistence of malignancies as an increased risk of malignancies has been reported in SLE patients (1). Here we report a female SLE patient with multiple nodular lesions in the lungs and bones, which first made us suspect a malignancy or infection.…”
Section: Introductionmentioning
confidence: 78%
“…A multicentre international cohort study was performed by Bin J et al [24] to provide a brief report of the lung cancer cases from an SLE cohort and concluded that histological pattern of distribution of lung cancer were similar in SLE cohort and in general population but incidence of malignancy was slightly high in SLE cohorts when compared with general population with a standardized incidence rate 1.37, but hasn't thrown light on the exact mechanism of coexistence [24]. Incidence of SLE and lung cancer was higher in women [25][26][27][28]. The reported incidence of lung cancers coexisting with SLE or vice verse in Indian population compared to western population are very few, the incidence is being less than 2% [1].…”
Section: Discussionmentioning
confidence: 99%